2014
DOI: 10.1007/s00220-014-1995-z
|View full text |Cite
|
Sign up to set email alerts
|

Global Gauge Anomalies in Coset Models of Conformal Field Theory

Abstract: We study the occurrence of global gauge anomalies in the coset models of two-dimensional conformal field theory that are based on gauged WZW models. A complete classification of the non-anomalous theories for a wide family of gauged rigid adjoint or twisted-adjoint symmetries of WZW models is achieved with the help of Dynkin's classification of Lie subalgebras of simple Lie algebras.Considering each subgroup Z and the corresponding values of a 1 , a 2 ,ã 1 , andã 2 , and recalling the admissible values (3.33) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
4
1
Order By: Relevance
“…Moreover, it is shown that the U (1) boson obtains mass term by gauging out background gauge field. This result itself is quite different from G/G coset WZW model description which results in topological field theory by gauging out the background gauge field 20,21 . Therefore, it is necessary to modify the bosonic gauged WZW models so that they can produce a consistent path integral with their fermionic counterparts.…”
Section: Introductioncontrasting
confidence: 63%
“…Moreover, it is shown that the U (1) boson obtains mass term by gauging out background gauge field. This result itself is quite different from G/G coset WZW model description which results in topological field theory by gauging out the background gauge field 20,21 . Therefore, it is necessary to modify the bosonic gauged WZW models so that they can produce a consistent path integral with their fermionic counterparts.…”
Section: Introductioncontrasting
confidence: 63%
“…Finally, the proof of Theorem 4.1 involves the adjoint Polyakov-Wiegmann formula from Theorem 3.5 concerning Wess-Zumino amplitudes for products of fields, which mostly relies on the homotopy classes of the considered maps, characterized by Lemmas A.1 and A.2. As it was pointed out in Remark 3.6, the Polyakov-Wiegmann formula and its adjoint version can be anomalous, so that that the Wess-Zumino amplitude of a product map gh is not easily related to the ones of g and h. This part of our work also constitutes a first step towards a classification of anomalies for U (N )-valued fields, that generalizes the one for simple Lie groups obtained using gerbe techniques [21,15], for what concerns the Polyakov-Wiegmann formula, its adjoint version, and beyond.…”
Section: Discussionmentioning
confidence: 65%
“…Such an obstruction, or anomaly, was already studied in detail for every closed compact Σ and every compact simple Lie group in [21], and Theorem 3.5 above states that the adjoint Polyakov-Wiegmann formula has no anomaly for Σ = T 2 and G = U (N ). More generally, a detailed classification for simple Lie groups in the context of gauged Wess-Zumino-Witten models shows that the corresponding adjoint version can also be anomalous in some cases [15]. ♦…”
Section: Adjoint Polyakov-wiegmann Formulamentioning
confidence: 99%
“…It is possible that the quantization conditions on k, m, n, p could alternatively be obtained by analyzing the global consistency of the gauging, see e.g. [61][62][63][64][65]. In the next section we will instead proceed to analyze the global geometry of the gauged target space.…”
Section: Jhep08(2021)011mentioning
confidence: 99%